Taxonomy of wild birds’ lice at the campus of Chittagong University, Chattogram, Bangladesh (Bangladesh Journal of Zoology, 2022)
Lice of five wild bird species, of diversified feeding habits and phylogeny viz., Sturnus contra, Acridotheres tristis, A. fuscus, Pycnonotus cafer and Streptopelia chinensis – have been investigated between 2014 and 2018 from the Chittagong University Campus and adjoining areas. A total of six lice species, viz., Menacanthus eurysternus (Burmeister), Sturnidoecus sturni (Clay), Bruelia zohrae (Ansari), Myrsidea kathleenae (Hellenthal and Price), Columbicola turturis (Uchida) and Nitzschiella lativentris (Uchida), were identified and described. Among them, five were strictly host specific – S. sturni (in S. contra), B. zohrae (in A. fuscus), M. kathleenae (in P. cafer), C. turturis (in S. chinensis), and N. lativentris (in S. chinensis). The remaining species, M. eurysternus, had wide specificity – occurring in all the three sturnid species investigated, i.e., S. contra, A. tristis and A. fuscus. Closely related hosts were found to share similar parasite species whereas unrelated host possess completely different lice species. Of the five hosts, three (S. contra, A. fuscus, and Streptopelia chinensis) were found to be infested by two lice species each, whereas, A. tristis and P. cafer hosted by a single lice species each.Bangladesh J. Zool. 50 (1): 51-66, 2022